Service Management Role In Improving Educational Quality - Rini Susilowati; Titi Hendrawati; Acep Nurulah; Ade Marfuddin (Badan Penerbit STIEPARI Press, 2023)
The purpose of this study is to ascertain how service management might be used to raise the standard of inclusive education. The study was conducted at MI Al-Biruni Bandung, SD Ibnu Sina Bandung, and SDI Scholar Muda Bandung. This study employs a qualitative case study methodology. The study's findings demonstrate how to manage inclusive education services by giving students with special needs (PDBK) the infrastructure and facilities they need, hiring qualified teachers, adapting the curriculum and assessment methods for GDPK, and fostering a positive learning environment. According to the goals and objectives of the schools, each of the three educational institutions has a unique approach to implementing service management. Although the objectives of education may vary, they generally remain relate to the criteria of quality outlined in the relevant laws and regulations.